THE EFFECTS OF AEROBIC EXERCISE AND DETRAINING ON LEFT VENTRICULAR CARDIOMYOCYTE APOPTOSIS - Putri, Mustika (Lembaga Penelitian Universitas YARSI, 2016)
Apoptosis can occur in several pathological heart conditions. Physical exercise, particularly aerobic exercise may reduce apoptosis on cardiomyocytes. Detraining can restore adaptation after exercise. This study aimed to see the effect of aerobic exercise and detraining on left ventricular cardiomyocyte apoptosis using caspase-3 as the parameter.This was an in vivo experimental study on Wistar rats Rattus Novergicus. Rats divided to 8 groups: 4 sedentary control groups: 4-week (C4), 8-week (C4D), 12-week (C12), 16-week control (C12D), and 4 aerobic exercise treatment groups: 4-week (A4) and 12-week (A12), and 4 12-week post aerobic exercise treatment followed by 4 weeks detraining (A4D, A12D). Caspase-3 protein in rat left ventricular tissue was identified by immunohistochemistry staining. Data were analized with ANOVA test using SPSS proggramme version 20.Data analysis showed an increase percentage of caspase-3 expression on post-aerobic exercise (A), be compared with conntrol group (C) (A4 65,3%±2,54 vs K4 6,4%±1,78, p 0,001; A12 41,8%±3,21 vs K12 5,7%±0,88, p 0,001; A4D 66,6%±1,89 vs K4D 8,6%±3,60, p 0,001; A12D 45,1%±1,50 vs K12D 7,4%±2,06, p 0,001). Percentage of caspase-3 expression was not different on post-aerobc exercise (A), be compare with detraining group (A4D 66,6%±1,89% vs A4 65,4%±2,54, p=0,484; A12D 45,1%±1,50 vs A12 41,8%±3,21, p=0,063). Percentage of caspase-3 expression on post 4-week aerobic exercise group was higher than post12-week aerobic exercise (A4 65,4%±2,54 vs A12 41,8%±3,21, p 0,001).In conclusion, the aerobic exercise protocol used in this study, was not found to decrease left ventricular cardiomyocyte apoptosis. Detraining did not increase left ventricular cardiomyocyte apoptosis.